MOTHER AS WEAPON: REFLECTION ON FAMILIAL SUICIDE TERRORISM IN INDONESIA - Sahrasad, Herdi; Tabrani, Dedy; Chaidar, Al; Zakaria, Mursyidin; Ansari, Teuku Syahrul (Aceh Anthropological Journal, 2019)
The article describes about the nuclear family (keluarga batih) suicide bombings. This kind of terrorism called the familial terrorism which carrying out the nuclear family. The world is shocked by the sacrifice of the lives of those who struggle pragmatically to achieve the paradise promised by God. However, a familial suicide bombing left a mark of significant lessons and explanations so that the world community understood why all this happened. So that the phenomenon of family suicide bombing shifts the landscape of extreme violence that occurred in Indonesia, which was previously dominated by men and the action is usually carried out alone or in groups in action, and does not involve family members especially children. Women are also considered to be adept at manipulating situations so that opponents are not easily suspected for security reasons. And do not forget, the trend shows that in Indonesia (Southeast Asia) terrorist threats involving women tend to increase, whether in the form of actions of married couples or with children, the tendency of such terrorism is 'trending'. Therefore, going forward, if this reflection is not too missed, civil society and the state must strive to prevent, be alert and overcome the increasing role of women in acts of terrorism because of the strong trend that women's roles are increasingly optimized and maximized by the terrorist actors in this sadistic, dramatic and brutal action.